‘NOLI ME TANGERE’: WHY JOHN MEIER WON'T TOUCH THE RISEN LORD - Craig, William Lane (Heythrop journal, 2009)
John Meier distinguishes ‘the real Jesus’ from ‘the historical Jesus’. Meier claims that whatever happened to the real Jesus after his death, his resurrection cannot belong to the historical Jesus because that event is in principle not open to the observation of any observer. But why think that the resurrection is not observable in this way? Meier finds justification in Gerald O'Collins' view that although the resurrection of Jesus is a real event, it is not an event in space and time and hence should not be called historical, since a necessary condition of historical occurrences is that they are known to have happened in our space-time continuum. Is this a good argument for the resurrection's being in principle excludable from the historical Jesus? A close examination of the argument reveals that it is not and that Meier's adoption of such a procedure contradicts Meier's own historical methodology.